The antifouling and fouling-release performance of hyperbranched fluoropolymer (HBFP)-poly(ethylene glycol) (PEG) composite coatings evaluated by adsorption of biomacromolecules and the green fouling alga Ulva - Gudipati, Chakravarthy S (Langmuir : the ACS journal of surfaces and colloids, 2005)
Cross-linked hyperbranched fluoropolymer (HBFP) and poly(ethylene glycol) (PEG) amphiphilic networks with PEG weight percentages of 14% (HBFP-PEG14), 29% (HBFP-PEG29), 45% (HBFP-PEG45), and 55% (HBFP-PEG55) were prepared on 3-aminopropyl)triethoxysilane (3-APS) functionalized microscope glass slides for marine antifouling and fouling-release applications. The surface-free energies (gamma(s)), polar (gamma(s)(p) and gamma(s)(AB)), and dispersion (gamma(s)(d) and gamma(s)(LW)) components were evaluated using advancing contact angles by two-liquid geometric-mean and three-liquid Lifshitz-van der Waals acid-base approaches. The HBFP coating exhibited a low surface energy of 22 mJ/m(2), while the gamma(s) and gamma(s)(p) of the cross-linked HBFP-PEG coatings increased proportionally with the PEG weight percentages in the networks. The adsorption of bovine serum albumin (BSA), lectin from Codium fragile (CFL), lipopolysaccharides from Escherichia coli (LPSE) and Salmonella minnesota (LPSS) upon glass, APS-glass, HBFP, PEG, and the cross-linked HBFP-PEG network coatings were investigated by fluorescence microscopy. The marine antifouling and fouling-release properties of the cross-linked HBFP-PEG coatings were evaluated by settlement and release assays involving zoospores of green fouling alga Ulva (syn. Enteromorpha; Hayden, H. S.; Blomster, J.; Maggs, C. A.; Silva, P. C.; Stanhope, M. J.; Waaland, J. R. Eur. J. Phycol. 2003, 38, 277). The growth and release of Ulva sporelings were also investigated upon the HBFP-PEG45 coating in comparison to a poly(dimethylsiloxane) elastomer (PDMSE) standard material. Of the heterogeneous cross-linked network coatings, the maximum resistances to protein, lipopolysaccharide, and Ulva zoospore adhesion, as well as the best zoospore and sporeling release properties, were recorded for the HBFP-PEG45 coating. This material also exhibited better performance than did a standard PDMSE coating, suggesting its unique applicability in fouling-resistance applications